2013
DOI: 10.1007/s11739-013-0983-1
|View full text |Cite
|
Sign up to set email alerts
|

Cardio pump reloaded: in-hospital resuscitation during transport

Abstract: High-quality chest compressions are crucial during resuscitation if a positive outcome is to be achieved. Sometimes a patient must be transported within the hospital while chest compressions are being performed. We compared different chest compression devices [animax mono (AM), AutoPulse(®) (AP) and LUCAS2™ (L2)] with manual chest compression using a manikin during transport from a fifth floor ward to the cardiac catheterization laboratory in the basement. Chest compressions were interrupted for 10.7 s to set … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…However, like the studies conducted by Gassler et al 9 and Ventzke et al, 10 the time from the start command to the first compression was longer than 10 seconds in the CPR-MCCD group. Compared to anesthesiology residents, emergency residents took less time to prepare the device.…”
Section: Cpr-s Versus Cpr-mccd ‡supporting
confidence: 50%
See 2 more Smart Citations
“…However, like the studies conducted by Gassler et al 9 and Ventzke et al, 10 the time from the start command to the first compression was longer than 10 seconds in the CPR-MCCD group. Compared to anesthesiology residents, emergency residents took less time to prepare the device.…”
Section: Cpr-s Versus Cpr-mccd ‡supporting
confidence: 50%
“…2 For the CPR-S and CPR-W methods, the average number of compressions per minute was found to be higher than the numbers recommended in the ERC and AHA guidelines. Furthermore, Gassler et al 9 and Ventzke et al 10 found a significantly higher number of compressions per minute when comparing the efficacy of various MCCDs during patient transport. This was likely because it was difficult to concentrate on the number of compressions during dynamic patient transport.…”
Section: Cpr-s Versus Cpr-mccd ‡mentioning
confidence: 99%
See 1 more Smart Citation
“…Transportation of patients in CPR in and out the hospital is a frequent contingency. Ventzke et al 65 compared the performance of Animax, LUCAS 2, AutoPulse, and manual CPR during the transportation of a manikin from the fifth floor to the basement of the same hospital. Unfortunately, they did not give information about the training of the staff involved in the trial.…”
Section: The Situational Factorsmentioning
confidence: 99%